Lymphocyte-specific protein 1 regulates mechanosensory oscillation of podosomes and actin isoform-based actomyosin symmetry breaking - Pasquale Cervero (Nature Portfolio, 2018)
The actomyosin cytoskeleton plays an important role in polarised cell migration. Here the authors identify lymphocyte-specific protein (LSP)-1 as a regulator of actomyosin contractility in macrophages, by competing with supervillin for myosin IIA activators acting specifically on the β-actin isoform.